Identifikasi Pelaksanaan Assessment diagnostic Kurikulum Merdeka Pembelajaran Pendidikan Jasmani Sekolah Dasar di Kecamatan Gunungpati Kota Semarang - Muhammad Budi Wijaya; Wahyu Ragil Kurniawan; Ranu Baskora Aji Putra; Moch Fahmi Abdulaziz (Indonesian Journal for Physical Education and Sport, 2024)
The implementation of diagnostic assessments conducted by Physical Education teachers is stillrelatively low. The purpose of this study is to determine teacher understanding, teacher steps tocompile diagnostic assessments and how to apply diagnostic assessments through the arrangementof steps that have been made by teachers based on the Independent Curriculum. The research method used is a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results of this study were from five Physical Education teachers, three understood diagnostic assessment well, four of them could provide explanations related to the steps for preparing diagnostic assessments, and only two teachers had applied the Curriculum Merdeka diagnostic assessment in Physical Education learning. The conclusion of this study is that the application of the Independent Curriculum diagnostic assessment of Physical Education learning for Physical Education teachers in A-accredited State Elementary Schools in the Dewi Kunti Cluster, Gunungpati District, Semarang City is still low